ANALISIS LINGKUNGAN ORGANISASI DALAM MENUNJANG KINERJA ORGANISASI PUBLIK (Studi pada Dinas Perdagangan dan Pasar Kota Metro Lampung) - Adrian Tawai; Hendriawan Hendriawan (Universitas Bandar Lampung (UBL), 2019)
The problems in this research are: (1) How is the Environmental Condition of the Organization at the Metro City Trade and Market Office. (2) What aspects support and hinder the Organizational Environment in Supporting Public Organization Performance at the Metro City Trade and Market Office.The research method used in this research is descriptive qualitative method. The use of this method is to describe the Organizational Environment in Supporting the Performance of Public Organizations at the Metro City Trade and Market Office, to study qualitatively, how all data is obtained directly from informants in the field using interviews and document studies.The results show that the organizational environment of the Metro City Trade and Market Office is one of the causes of success in carrying out a job, because the organizational environment can affect workers, especially the organizational environment that is psychological in nature. The organizational environment at the Metro City Trade and Market Office aims to provide maximum work comfort, so that employees in providing quality services, in the sense that if employees work and the results of the work get appreciation and recognition, then the work must be of high quality.Supporting and inhibiting aspects in efforts to improve the organizational environment at the Metro City Education and Culture Office. These aspects can occur both internally and externally to the organization. Internal factors include elements contained in the body of the organization, namely the Metro City Trade and Market Office. Then the external factors that come from outside the Metro City Trade and Market Office, such as local governments, relevant agencies and the community. This happens because a good organizational environment has been strived for, but it has not materialized as expected because there are still employees who are not fully comfortable with the existing organizational environment, such as air circulation, noise in the workplace.